PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PELAYANAN PURNA JUAL TERHADAP LOYALITAS KONSUMEN (Studi pada Pengguna Handphone Samsung di Kota Semarang) - Putra, Endica Arnandhitya; Nurseto, Sendhang (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
This research is aimed to know the impact of brand image, product quality and after sales service to the Samsung handphone customers loyalty in Semarang. The type of this research is explanatory research,the data collecting technique is quisioners with 100 respondends as the sample, purposive sampling and accidental technique are used. The chosen respondends are customers who buy and use Samsung handphone in Semarang. Methodology used to analyze the main data is validity test, reliability test, correlation coefficient, determination coefficient, simple linear regression, double linear regression and significance test (test t and F).The research result shows that brand image has signifficance impact to customers loyalty for 28.1%. The product quality has 38,9% impact on customer loyalty. After sales service has 25,4 % impact to customers loyalty. Simultaneously, brand image,product quality, and aftersales service has signifficant impact to customers loyalty for 48,1 % while the rest is influnced by other factors beside brand image, product quality, and after sales service. It means that the better the brand image,product quality and after sales service the higher the loyalty of Samsung handphone customers.